ANALISIS READINESS SISTEM INFORMASI KEPEGAWAIAN - Ivan Dwi Fibrian (SAINTEKBU, 2019)
Computer and Internet Study Center Unipdu is developing a Personnel Management Information System in accordance with the current situation, therefore it is necessary to do a Readiness Analysis on the Personnel Management Information System before it is implemented, this is intended to measure the readiness of staff in implementing the system. This research was conducted using the STOPE Framework approach which only focused on the level of user readiness, namely the Unipdu Jombang Staffing Administration Bureau. The results of data processing obtained from the distribution of questionnaires to staff and lecturers at Uiversitas Pesantren Tinggi Darul Ulum, were obtained that from five domains there were 2 (two) domains that received readiness scores at level 3 (ready) on scale 4, namely People, Environment, while Strategy domains. Technology, and Organization get value of readiness at level 4 (very ready) on a scale of 4. Overall or at the level of the STOPE framework, Uiversitas Pesantren Tinggi Darul Ulum is ranked 3 (ready) to implement the Personnel Management Information System. But there are still some weaknesses at the level of subdomains and sub-subdomains that must get attention and improvement in implementing the Personnel Management Information System.